Radiofrequency Ablation of Drug Refractory Ventricular Tachycardia Related to Cocaine Use: A Feasibility, Safety, and Efficacy Study. (30th May 2014) - LAKKIREDDY, DHANUNJAYA; KANMANTHAREDDY, ARUN; BIRIA, MAZDA; MADHU REDDY, YERUVA; PILLARISETTI, JAYASREE; MAHAPATRA, SRIJOY; BERENBOM, LOREN; CHINITZ, LARRY; ATKINS, DONITA; BOMMANA, SUDHARANI; TUNG, RODERICK; DI BIASE, LUIGI; et al.
RF Ablation of VT in Chronic Cocaine Users Background Cocaine use is a known but rare cause of cardiac arrhythmias. Ventricular arrhythmias related to cocaine may not respond to antiarrhythmic drugs and may need treatment with radiofrequency ablation. Objectives We describe the clinical and electrophysiological characteristics of cocaine‐related ventricular tachycardia (VT) from a multicenter registry. Methods Subjects presenting with VT related to cocaine use and being considered for radiofrequency ablation have been included in the study. Patients who were refractory to maximal medical therapy underwent radiofrequency ablation of the VT. Clinical, procedural variables, efficacy, and safety outcomes were assessed. Results A total of 14 subjects met study criteria (age 44 ± 13, range 18‐ to 68‐year‐old with 79% male, 71% Caucasian). MRI showed evidence of scar only in 43% of patients (6/14). The mechanism of VT was focal in 50% (n = 7) and scar related reentry in 50% (n = 7) based on 3D mapping. The mean VT cycle length was 429 ± 96 milliseconds. The site of origin was epicardial in 16% (3/18) of VTs. Most clinical VTs were hemodynamically stable (75%). Mean ejection fraction at the time of admission was 44 ± 14%. Duration of procedure was 289 ± 50 minutes. One subject developed pericardial tamponade requiring drainage. At 18 ± 11 months follow‐up, freedom from arrhythmia was seen in 86% (1 case lost to follow‐up and 2 died). Conclusion Radiofrequency ablation is not only feasible but also safe and effective in patients who have drug refractory VT related to chronic cocaine use.